2018
DOI: 10.3390/ma11050803
|View full text |Cite
|
Sign up to set email alerts
|

Highly-Stable Li4Ti5O12 Anodes Obtained by Atomic-Layer-Deposited Al2O3

Abstract: LTO (Li4Ti5O12) has been highlighted as anode material for next-generation lithium ion secondary batteries due to advantages such as a high rate capability, excellent cyclic performance, and safety. However, the generation of gases from undesired reactions between the electrode surface and the electrolyte has restricted the application of LTO as a negative electrode in Li-ion batteries in electric vehicles (EVs) and energy storage systems (ESS). As the generation of gases from LTO tends to be accelerated at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…As mentioned above with the Micro-Raman analyses of burned LTO@PTCLi 4 samples, the shape of the 2D band suggests that the carbon coating was composed of a few layers of carbon atoms. 65 If we take into account the reported value for the thickness of a PTCDA monolayer, which is approximately 0.32 nm, 38,66 then the carbon coating should be composed of at least six to seven layers of perylene-like carbon. A rough calculation, considering the largest lattice parameter of the PTCDA monoclinic crystal (P2 1 /c space group, approximately 2 nm), 38 quantity of carbon estimated by TGA (0.89 wt%), and the BET surface area for the LTO sample (see Fig.…”
Section: Materials Advancesmentioning
confidence: 99%
“…As mentioned above with the Micro-Raman analyses of burned LTO@PTCLi 4 samples, the shape of the 2D band suggests that the carbon coating was composed of a few layers of carbon atoms. 65 If we take into account the reported value for the thickness of a PTCDA monolayer, which is approximately 0.32 nm, 38,66 then the carbon coating should be composed of at least six to seven layers of perylene-like carbon. A rough calculation, considering the largest lattice parameter of the PTCDA monoclinic crystal (P2 1 /c space group, approximately 2 nm), 38 quantity of carbon estimated by TGA (0.89 wt%), and the BET surface area for the LTO sample (see Fig.…”
Section: Materials Advancesmentioning
confidence: 99%
“…Whether a stable SEI can be formed on the surface of an LTO electrode is a debatable topic. [7][8][9] Theoretically, the SEI cannot form on the LTO electrode since its redox potential of 1.55 V vs Li/Li + is above the reduction potential of most electrolytes 10 ; however, many researchers have identified the existence of an SEI on the surface of the LTO electrode using X-ray photoelectron spectroscopy and depth profiling techniques. [11][12][13][14][15][16][17][18] Gauthier et al 11 showed that the SEI on LTO is composed of organic (polyethylene oxides, oxalates) and inorganic species (LiF, phosphates and fluorophosphates), in which the composition and thickness of the SEI are greatly affected when using different electrodes.…”
mentioning
confidence: 99%
“…Rapid capacity fading in NMC–NMC cells has previously been observed at 30 °C and also in NMC442–NMC442 cells cycled at 40 °C, attributed to side‐reactions rather than mechanical degradation . The fading in the LTO–LTO cell is likely related to gas formation, which has been shown to be prominent at elevated temperatures . The low capacity retention and coulombic efficiency in the full cell cycled at 55 °C indicate continuous side‐reactions and that the surface layer formation on the electrodes is not suppressing the parasitic reactions.…”
Section: Resultsmentioning
confidence: 76%